Cultivo de Chlorella vulgaris em diferentes concentrações de vinhaça e fontes de luz - Souza, Andréa Cristina Moralez de (Universidade Federal de São Carlos, 2016)
The effluent from the sugarcane (sugar and ethanol) industry known as vinasse presents high content of organic matter and nutrients that can be used in the cultivation of microalgae with the advantages of low cost and reuse of byproducts. This work proposes to investigate the best cultivation condition of Chlorella vulgaris (BEYERINCK, 1890) in agroecological vinasse treated and diluted in concentrations from 10% to 60%. It is noted that the vinasse carries microorganisms as bacteria and yeasts, and despite previous treatment of algal cultures, other microorganisms were always present. For algal growth, we initially tested different light sources (fluorescent, hot white LED and hot white with red LED). It was guaranteed the same light intensity (120μmols m 2s-1) for any of the vinasse concentrations. It was assessed the algal cell density, the pH and conductivity over 96 hours. The best result for growth of C. vulgaris was obtained in vinasse 20% in the presence of hot white and red LED with a growth rate (1.45 d-1), higher than the control (1.29 d-1). In a next step it was performed the microalgae cultivation in the best condition tested (20% vinasse) to evaluate the photosynthetic and biochemical parameters of biomass produced in addition to the physicochemical characterization of vinasse before and after cultivation. The results showed a reduction of the photosynthetic efficiency and chlorophyll concentration during the experimental period, suggesting mixotrophic metabolism possibly due to the presence of organic carbon. We observed that the biomass production was 40% higher in the vinasse in culture as compared to the control. The production of proteins and fatty acids was also higher in the biomass held in vinasse than in the control. The cultivation of the organisms led to a significant reduction of nitrogen levels (98%) and potassium (70%) in organic vinasse. This research has shown that microalgae cultivation in vinasse reduced the nutrient content of the residue, this factor has high impact when discarded in the environment and produced a biomass with high protein content and the presence of fatty acids that confer high commercial value, it can be investigated for the production of animal feed. The academic experience related to this study was also contributor of formal education in high school from a public school.
Keywords: Chlorella vulgaris; Efluentes; Microalgas; Vinhaça; Chlorella vulgaris; Waste; Microalgae; Vinasse; CIENCIAS BIOLOGICAS::BOTANICA